Levels of enamel erosion for the application of bleaching agents - Díaz Soriano, Ana (2009)
Dental bleaching systems and its use of toothpaste with bleaching agents lead to search the effect of these systems on the enamel surface. Scientific evidence shows that these systems can provoke an answer in chemical shucture of the dental enamel with loss of calcium . The concentration of calcium was measured in ppm in 27 crowns of human bicuspids. The enamel erosion was measured through the liberation of calcium salts into teeth in two kinds of bleaching toothpastes : Crest whitening and Colgate Maxwhite, and they were compared with the gold standard (carbamide peroxide 20%) . Measurements of calcium concentration were made in 12 h, 24 h and 7 d. Atomic absorption spectophotometry was used to determine the calcium concentration. ANOVA analysis indicates that Crest Whitening toothpaste shows more concentration of calcium salts in enamel surface than Colgate Maxwhite which contains peroxide ,in the same way that carbamide peroxide gel that it is used in professional dental system.